Hydration number and allied parameters of aqueous solutions of ammonium bromide through ultrasonic study - J.H. Rakini Chandrasekaran; S. Nithiyanantham (Vietnam Journal of Science, Technology and Engineering, 2024)
Ammonium bromide, a water-soluble wood preservative used in pharmaceutical preparations, is the focus of this economic study aimed at understanding its physical properties in aqueous solutions. A straightforward and reliable method for examining interactions between molecules in liquids and solutions is ultrasonic research. When ultrasonic waves pass through liquids, they disturb the equilibrium between the molecules of the solute and solvent. Ion-ion and ion-solvent interactions are just two aspects of solvation chemistry that ultrasonic velocity measurement can elucidate. This study investigates the hydration number of aqueous solutions of ammonium bromide at temperatures ranging from 35 to 55°C, assessing both density and ultrasonic velocity across various concentrations. From the adiabatic compressibility, the hydration number and related parameters are derived, all of which are sensitive to changes in concentration and temperature. Thus, we explore how these parameters vary with changes in temperature and concentration, providing insight into the interactions of ions and molecules in the solutions, as well as their molecular structure.